Facebook Nation Total Information Awareness - Lee, Newton. (Springer New York : Imprint: Springer, 2013)
President Barack Obama, in his 2011 State of the Union Address, called America "the nation of Edison and the Wright brothers" and "of Google and Facebook." U.S. Chief Information Officer, Steven VanRoekel, said that America has become a "Facebook nation" that demands increased transparency and interactivity from the federal government. Facebook as a nation in 2012 would be the third largest country in the world with over 900 million citizens, after China and India. This book portrays the social media ecosystem as a world of increasing Total Information Awareness, which is essentially a civilian version of the controversial Total Information Awareness program unveiled in 2002 by the Defense Advanced Research Projects Agency (DARPA) at the U.S. Department of Defense. Back in the 60's, DARPA initiated and funded the research and development of Advanced Research Projects Agency Network (ARPANET) that went online in 1969. The success of ARPANET gave rise to the global commercial Internet in the 90's and the new generation of Fortune 500 companies today including Amazon.com, Google, eBay, and Yahoo!. As if life comes full circle in the 21st century, private businesses and the ubiquity of social networks such as Facebook, Google+, Twitter, and YouTube are creating the technologies and infrastructures necessary for the DARPA-proposed Total Information Awareness program. WikiLeaks founder Julian Assange called Facebook "the most appalling spying machine that has ever been invented." Indeed, military and civilian technologies have interwoven into every fabric of our society, as Facebook co-founder and CEO Mark Zuckerberg said, "We exist at the intersection of technology and social issues." This book offers discourse and practical advice on the privacy issue in the age of big data, the rise of Facebook nation, and Total Information Awareness. Opening with President Ronald Reagan's 1984 National Security Decision Directive and ending with George Orwell's novel 1984, the author takes us on a roller-coaster ride through Facebook's botched IPO, Carrier IQ, Kony 2012, SOPA/PIPA blackout, cyber bullying, crime fighting, and a host of other timely issues facing our Facebook nation. Social media strategists, information architects, social scientists, policymakers, and academic scholars in the Program in Science, Technology, and Society (STS) will find this book a valuable asset.